Workability and Life Satisfaction: Effects of Workers' Positive Perceptions on Their Return to Jobs - Dongsuk Kang (Elsevier, 2022)
Background: The death rate of workers due to industrial accidents in South Korea (3.61 persons in 2017) is higher than the Organization for Economic Cooperation and Development average (2.43) and the fifth highest among Organization for Economic Cooperation and Development member countries. Although the pandemic of novel coronavirus (COVID-19) has changed, the socioeconomic aspects of Korean society, the number of Koreans suffering accidents and the number of deaths in 2020 have increased. It is necessary to take measures to prevent accidents and make comprehensive efforts to return to work. This study proposes research questions about the effect of workers' positive perception on whether to work after accidents and the impact of the experience of rehabilitation services on the return to work. Methods: This research performed a panel logistic regression analysis using data on workers' compensation insurance in Korea for two years (2018-2019). Results: This research finds that workers' positive perceptions of workability and life satisfaction contributed affirmatively to their re-employment. Several factors related to employment (e.g., work period, the number of job qualifications) also positively affect their return to work. However, the experience of rehabilitation services did not have a significant effect on re-employment. The variables of their health conditions (e.g., disability grade, feelings of health problems, age) negatively influenced their return to jobs. Conclusion: These results suggest the importance of workers' mental recovery and the need to innovate rehabilitation services for their employment. Positive thinking and self-rehabilitation could be critical for workers, parallel with social welfare policies.